REDISCOVERY AND TAXONOMIC REASSESSMENT OF FOUR ANGIOSPERMS IN THE SAVANNAS OF JALAPÃO, CENTRAL BRAZIL - Antar, G. M.; Santos, M. F.; Sano, P. T. (Edinburgh journal of botany, 2018)
Globally, the Cerrado is the most diverse savanna in terms of plant species, as well as one of the most threatened as the result of human impact; it is therefore considered a priority area for conservation. Some areas of the Cerrado have still not been subject to botanical collections and detailed studies, the Jalapão region being one of these. We describe four recently rediscovered species previously known only from type specimens collected at least 160 years ago: Hyptis caduca Epling (Lamiaceae), Duguetia rotundifolia R.E.Fr. (Annonaceae), Diospyros ovalis Hiern (Ebenaceae) and Rhabdodendron gardnerianum (Benth.) Sandwith (Rhabdodendraceae). Comments on their ecology, conservation status and occurrence are provided, together with a distribution map. New morphological data have been recorded, and all species are considered to be under some degree of threat. These rediscoveries highlight the importance of further fieldwork in poorly sampled and highly biodiverse regions such as Jalapão and neighbouring areas, as well as the urgent need for conservation of the highly threatened Cerrado biome.